Eskatologis Dalam Wayang Purwa: Studi Kasus Kematian Pandu - YB Rahno Triyogo (Institut Seni Indonesia Surakarta, 2021)
Eschatology is a branch of science that talks about the final things of human life, namely death and life after death. Pandu is a character who experiences a new life after experiencing death. According to the classical view, he should be in hell forever, but because of the struggle of his second son named Bratasena and Permadi, he was freed from hell and obtained a heavenly life. The methods used were data collection, literature study, and interviews. An eschatological approach was used and the result was that Pandu experienced hell suffering because of his speech. denying speech (hypocrisy). Bratasena’s struggle in trying to free his parents from hell reflects his devotion to his parents. Together with Arjuna, his sister and the angels they managed to penetrate the heavens of the throne of the gods. Their struggle can be understood as an inner dialogue, or human prayer with the Creator asking for deliverance.